Tokenization of Dinar and Dirham: Potential and Implications in the Islamic Digital Financial System - Hutagalung, Muhammad Wandisyah R; Majid, M. Shabri Abd; Harahap, Isnaini (Journal of Islamic Financial Technology, 2024)
In the era of digitalization, the Islamic community faces challenges in integrating modern technology with Shariah principles in financial transactions. This study explores the potential and implications of tokenizing Dinar and Dirham within the Islamic digital financial system. Dinar and Dirham, currencies made of precious metals, can be tokenized using blockchain technology, enabling faster, more secure, and transparent transactions. Tokenization offers benefits such as transparency, security, efficiency, and financial inclusion, which are crucial in Islamic financial principles. However, the main challenges include regulation, Shariah compliance, technological infrastructure, and public awareness and education. Case studies from Dubai and Saudi Arabia demonstrate efforts and successes in asset tokenization. This study concludes that tokenization of Dinar and Dirham has significant potential to address the challenges of digitalization in Islamic finance, but requires collaboration among governments, financial institutions, and communities. Further research is needed to understand the long-term impact and practical application of tokenization in the Islamic financial system.